(untitled) - FAO (Rome, 1999)
This book aims toraise awareness of the role of wild plants in many farming systems, providing examples from different systems around the world. It describes the contribution of wild plants as a source of food, fuel wood, shelter, medicine and dyes and their role in income generation for the improved welfare of farm households and local people. Wild plants are also of paramount importance as sources of wild gerplasm that might enhance productivity, disease resistance, winter hardiness, drought survival and similar features of cultured species. The publication analyses the potential of wild species in farm households as well as the natural, social, economic, legal and institutional factors that constrain their use and development potential